PENGARUH TEKNOLOGI DIGITAL TERHADAP KEMAMPUAN SOSIAL ANAK DALAM KEHIDUPAN - Alfina Lailan (JIP: Jurnal Ilmu Pendidikan, 2025)
This article discusses the influence of digital technology on children's social skills in everyday life. In an increasingly digital era, children are increasingly familiar with various digital devices and platforms that bring both positive impacts and challenges to their social development. Digital technology helps children develop digital literacy, creativity, language skills and expand their social networks. However, excessive use without supervision can hinder face-to-face interactions, reduce the ability to manage emotions, and affect children's moral development. Therefore, the role of parents and educators is crucial in regulating the balanced use of technology and providing appropriate guidance. With the right approach, digital technology can be a tool that supports children's optimal social development, so that they can become a generation that is digitally proficient as well as socially and emotionally strong.